Anaerobic treatment of maize roots affects transcription of Adh1 and transcript stability. - Rowland, L J (1986)
Among the adaptations to stress exhibited by plants is the anaerobic response of roots, induced by submerging roots in water. The response consists of a programmed change in gene expression: proteins produced under aerobic conditions are no longer synthesized but are replaced by approximately 20 so-called anaerobic peptides (M. M. Sachs, M. Freeling, and R. Okimoto, Cell 20:761-767, 1980). The gene for maize alcohol dehydrogenase I (Adh1) is expressed at high levels under such conditions. We report here that changes in alcohol dehydrogenase I RNA levels in anaerobic roots are associated with changes in both transcription rate and transcript stability.